2016
DOI: 10.1021/acs.nanolett.6b02035
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Temperature Dependence of the Band Gap in Black Phosphorus

Abstract: Black Phosphorus (BP) has gained renewed attention due to its singular anisotropic electronic and optical properties that might be exploited for a wide range of technological applications. In this respect, the thermal properties are particularly important both to predict its room temperature operation and to determine its thermoelectric potential. From this point of view, one of the most spectacular and poorly understood phenomena is, indeed, the BP temperature-induced band-gap opening: when temperature is inc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
75
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(91 citation statements)
references
References 49 publications
15
75
1
Order By: Relevance
“…In a recent study, Wang et al [26] suggested that anisotropy in the thermal transport properties of bulk BP might be of particular interest in the fabrication of thermoelectric/optoelectronic devices. Recently, the temperature dependence of the band-gap of BP studied by ab initio calculations shed some light on the anomalous band-gap opening with the increasing volume [27]. The calculated temperature dependence of the lattice parameters along the armchair, zigzag and stacking directions had a good correspondence with the data shown in Figure 5a.…”
Section: Temperature-dependent Diffraction and Correlation Between Stsupporting
confidence: 59%
“…In a recent study, Wang et al [26] suggested that anisotropy in the thermal transport properties of bulk BP might be of particular interest in the fabrication of thermoelectric/optoelectronic devices. Recently, the temperature dependence of the band-gap of BP studied by ab initio calculations shed some light on the anomalous band-gap opening with the increasing volume [27]. The calculated temperature dependence of the lattice parameters along the armchair, zigzag and stacking directions had a good correspondence with the data shown in Figure 5a.…”
Section: Temperature-dependent Diffraction and Correlation Between Stsupporting
confidence: 59%
“…7). This anomalous temperature dependence has been recently explained considering the coupling of the electrons with low-frequency transverse optical modes [50]. We underline that this same temperature dependence of the gap must also be taken into account when performing temperature-dependent transport measurements to extract the value of the gap [25].…”
Section: Temperature Dependence Of the Optical Gap And Exciton Bimentioning
confidence: 61%
“…The remaining differences are ascribed to a combination of several effects such as intrinsic doping by impurities, weak interaction with lithium ions, the total energy resolution of the experiment (20 meV), and the fact that the transport gap was extracted by temperature dependent measurements. However, as was shown recently by Villegas and collaborators [50], the band gap has a strong and anomalous temperature dependence which could affect the transport results.…”
Section: Angle-resolved Photoemission Measurements Of the Three-mentioning
confidence: 81%
“…The lattice anharmonic contribution causes the lattice thermal expansion, constraining the band-gap to reduce further. However, we do not intend to compute this using a standard quasi-harmonic approximation approach [47], as it is well-known that unless there is no portion of the real part of the Eliashberg function difference taken between the lowest conduction and the top valence band (i.e, ℜ g 2 F C1 (ω) − g 2 F V1 (ω) ) that acquires a positive value, E g (T ) will always be much larger than E LT E g [18,48,49]. This is also an indirect proof to predict whether the gap decreases with T or not.…”
Section: Resultsmentioning
confidence: 99%